The youths' perceptions of sexuality in the Limpopo Province of South Africa - Thelmah X Maluleke (AOSIS, 2007)
This study was a qualitative, exploratory and descriptive study, conducted in the Vhembe District Municipality of the Limpopo Province in four selected villages. Opsomming Hierdie studie was 'n kwalitatiewe, verkennende en beskrywende studie, onderneem in die Vhembe Distrik Munisipaliteit van die Limpopo Provinsie, in vier uitgesoekte dorpies. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.